Current state of the Tekeli town: analysis of the positive and negative impacts (Journal of Geography and Environmental Management, 2017)
Study of territories with existing structure of industry and the determination of the direction of post-industrial development of territories is a topical issue for increasing the competitiveness of the Republic of Kazakhstan. They, in turn, will become a basis for the overall development of industry in the country. Compared to other cities with a multifunctional economy, the development of monotowns depends more on changes in the external environment, the state of the economy, the external market conjuncture, etc. This dependence is characterized as a blocking factor of sustainable development in our study. This article describes the current state of Tekelitown. As a result of analysis of key factors influencing the sustainable development of the town, a number of factors limiting the development of the town were revealed. The concentration of natural resources, physical and geographical features of the area are ighlighted as a priority for sustainable development; low level of diversification of the economy, accumulation of industrial waste, environmental threats are considered as a limiting factor in the development of the town. Models of the restoration and support of labor resources in monotowns in the conditions of the crisis are analyzed on the basis of the experience of foreign countries (Canada, USA, Germany, Russian Federation). The results and recommendations will serve as the basis for the economic development of town.